The Role of Small Dense Low-Density Lipoprotein in Diabetic Retinopathy - Jawad, Nawar M.; Mahmood, Halla G.; Mohammed, Abeer A. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Diabetic retinopathy is the primary ocular outcome of diabetes mellitus, a serious disease that significantly impacts global health. Microvascular complications arise from damage to small blood vessels, including retinopathy, nephropathy, cardiomyopathy, and neuropathy. Inconsistent findings exist in epidemiological research that specifically examines lipid levels and diabetic retinopathy. The small, dense Low-Density Lipoprotein particles are a specific subset of Low-Density Lipoprotein that possesses several pro-atherogenic characteristics.Objectives: to evaluate the usefulness of serum small dense low-density lipoprotein level as a biomarker for predicting patients with type II diabetes mellitus who suffer from proliferative and non-proliferative diabetic retinopathy. Methods: The study involved 160 individuals divided into four groups: 40 patients with non-proliferative diabetic retinopathy, 40 patients with proliferative diabetic retinopathy, 40 controlled diabetic patients without diabetic retinopathy, and 40 healthy controls. Student’s t-test and ANOVA were employed to compare the means between the groups.Results: The study revealed that small dense low-density lipoprotein levels in the proliferative diabetic retinopathy group were significantly higher than those in the non-proliferative diabetic retinopathy, diabetic without retinopathy, and healthy control groups. The mean and standard deviation in patients with proliferative diabetic retinopathy were 4.70±1.96 µmol/L, in non-proliferative diabetic retinopathy, it was 3.00±0.90 µmol/L, in diabetic patients without retinopathy, it was 2.51±0.53 µmol/L, and in healthy controls, it was 2.45± 0.48 µmol/L.Conclusion: Small, dense, low-density lipoprotein and triglycerides play roles in the progression of diabetic retinopathy in patients with type II diabetes mellitus. The small, dense, low-density lipoprotein and triglyceride levels were highest in the proliferative diabetic retinopathy and lowest in the healthy control.